Successful treatment with mezlocillin of a child infected by penicillin G-resistant Staphylococcus aureus - Kanra, Güler; Çağlar, M. Kazım; Dilmen, Uğur; Uluşahin, Namdar; Şenses, D. Ali; Ceyhan, Mehmet; Oran, Olcay (The Turkish Journal of Pediatrics, 1985)
A five-year-old boy with septic arthritis and purulent pericarditis caused by penicillin G-resistant Staphylococcus aureus which could not be controlled by different antibiotic combinations including penicillin, methicillin, cephalothin, gentamicin and netilmicin was successfully treated with mezlocillin. Although it has been reported that there is no antibacterial effect of mezlocillin on penicillin G-resistant Staphylococcus aureus, mezlocillin therapy was effective in our patient.
Keywords: mezlocillin; purulent pericarditis; septic arthritis; Staphylococcus aureus